Tanacetum vulgare L. (Tansy) as an effective bioresource with promising pharmacological effects from natural arsenal - ŞENKARDEŞ, İSMAİL (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
The Tanacetum genus is a big treasure with the presence of biologically-active compounds and members of this genus are widely used for the treatment of several diseases in traditional medicine system. Considering this fact, we aimed to analyze the extracts from Tanacetum vulgare L. in case of chemical profiles and biological effects. Chemical characterization was performed by using UHPLC-HRMS technique and showed the presence of several phytochemical groups (107 compounds were identified, including phenolic acids, flavonoids, terpenoids and fatty acids. Biological abilities were examined by using antioxidant (DPPH, ABTS, FRAP, CUPRAC, metal chelating and phosphomolybdenum assays) and enzyme inhibition (tyrosinase, amylase, glucosidase and cholinesterase) properties. Pharmaco-toxicological investigations were also performed with the aim to identify limits of biocompatibility, anti-oxidant and neuromodulatory effects, in hypothalamic HypoE22 cells. A bio-informatic analysis was also carried to unravel the putative protein-targets for the observed biological effects. Generally, the tested hexane and hydroalcoholic extracts displayed stronger activities in antioxidant and enzyme inhibitory assays, when compared with water. In addition, multivariate analysis was performed to understand the differences in both solvents and plant parts and we clearly observed the separation of these parameters. The extracts (10 mu g/mL) also stimulated DAT and inhibited TNF alpha and BDNF gene expression, in HypoE22 cells. In parallel, the extracts were also able to stimulate norepinephrine release from this cell line. By contrast, in the concentration range 50-100 mu g/mL, the extracts reduced the HypoE22 viability, thus demonstrating cytotoxicity at concentrations 5-10 fold higher compared to those effective as neuromodulatory. Our observations manifested that T. vulgare has several beneficial effects and it can be used as a potential natural raw material for designing further health-promoting applications in nutraceutical, cosmeceutical, and pharmaceutical areas.
Keywords: Tanacetum; Parthenolide; Biological effects; Bioinformatics; Health-promoting effects; IN-VITRO; CHLOROGENIC ACID; ESSENTIAL OILS; PARAVENTRICULAR NUCLEUS; INHIBITORY-ACTIVITIES; ANTIOXIDANT ACTIVITY; NEUROTROPHIC FACTOR; LIPID-PEROXIDATION; FLAVONOIDS; PLANTS